A 300-μW 1.9-GHz CMOS oscillator utilizing micromachined resonators. - Otis, B.P.
A low-power low-phase-noise 1.9-GHz RF oscillator is presented. The oscillator employs a single thin-film bulk acoustic wave resonator and was implemented in a standard 0.18-μm CMOS process. This paper addresses design issues involved in codesigning micromachined resonators with CMOS circuitry to realize ultralow-power RF transceiver components. The oscillator achieves a phase-noise performance of -100 dBc/Hz at 10-kHz offset, -120 dBc/Hz at 100-kHz offset, and -140 dBc/Hz at 1-MHz offset. The startup time of the oscillator is less than 1 μs. The oscillator core consumes 300 μA from a 1-V supply.
Keywords: 0.18 micron; 1 V; 1.9 GHz; 300 muA; 300 muW; CMOS circuit; MEMS resonator; RF transceiver; Low-power RF oscillator; Micromachining process; Phase noise; Startup time; Thin-film bulk acoustic wave resonator